The role of MYB34, MYB51 and MYB122 in the regulation of camalexin biosynthesis in Arabidopsis thaliana - Frerigmann, Henning; Glawischnig, Erich; Gigolashvili, Tamara (Frontiers in Plant Science, 2015)
The indolic phytoalexin camalexin is a crucial defence metabolite in the model plant Arabidopsis. Indolic phytoalexins and glucosinolates appear to have a common evolutionary origin and are interconnected on the biosynthetic level: a key intermediate in the biosynthesis of camalexin, indole-3-acetaldoxime (IAOx), is also required for the biosynthesis of indolic glucosinolates and is under tight control by the transcription factors MYB34, MYB51 and MYB122. The abundance of camalexin was strongly reduced in myb34/51 and myb51/122 double and in triple myb mutant, suggesting that these transcription factors are important in camalexin biosynthesis. Furthermore, expression of MYB51 and MYB122 was significantly increased by biotic and abiotic camalexin-inducing agents. Feeding of the triple myb34/51/122 mutant with IAOx or indole-3-acetonitrile largely restored camalexin biosynthesis. Conversely, tryptophan could not complement the low camalexin phenotype of this mutant, which supports a role for the three MYB factors in camalexin biosynthesis upstream of IAOx. Consistently expression of the camalexin biosynthesis genes CYP71B15/PAD3 and CYP71A13 was not negatively affected in the triple myb mutant and the MYBs could not activate pCYP71B15::uidA expression in trans-activation assays with cultured Arabidopsis cells. In conclusion, this study reveals the importance of MYB factors regulating the generation of IAOx as precursor of camalexin.